Development of the Android application Amaan Reading Books (AARAVI) to Build International Competitiveness of Students - Mustofa, Bisri (JURNAL IJ-ATL, 2023)
PAI teachers play a critical role in shaping Indonesian Islam. However, many PAI students lack sufficient skills in reading primary Islamic texts in Arabic, which is essential for their academic growth. To address this, the AARAVI (Proficient in Reading Books) application was developed as an Android-based learning tool to support Islamic Studies students in improving their reading skills. The research employed the ADDIE model, encompassing five stages: Analysis, Design, Development, Implementation, and Evaluation. The study involved 20 students from the 2020 batch of the Islamic Religious Education program at UIN Maulana Malik Ibrahim Malang, enrolled in the Qira'atul Kutub course. Data were collected through interviews, literature reviews, questionnaires, tests, and documentation. Data analysis techniques included descriptive analysis, quantitative analysis using percentage-based questionnaires, and statistical tests such as paired sample t-tests or Wilcoxon rank tests to evaluate pre- and post-test results. The findings demonstrate that AARAVI is a highly effective learning medium. Validation results from material experts yielded a score of 89%, media experts 83%, and student feedback 87%, all indicating high validity. Furthermore, there was a significant improvement in students’ reading abilities after using AARAVI, confirming its effectiveness. The application is thus deemed suitable for enhancing the reading skills of Islamic Education students, particularly at the beginner (mubtadi’in) level.